PENGARUH KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Operator PT. Indonesia Power Unit Bisnis Pembangkitan Semarang) - Kristiani, Diah Ayu; Pradhanawati, Ari; Wijayanto, Andi (Jurnal Ilmu Administrasi Bisnis, 2013)
PT. Indonesia Power UBP Semarang, part of the PT. Indonesia Power, is engaged in power generating of gas and steam. Companies desperately need the ability and motivation of the workforce, especially in the technical and operational machinery. As a measure of the progress of the company, PT. Indonesia Power perform employee performance assessment. It conducted each semester by filling Form Employee Performance by superiors. From the preliminary survey conducted by the researchers, it is known that the performance of the employees of PT. Indonesia Power UBP Semarang in 2011 has decreased. Performance of employees was reduced in grade 4 from 14.74% to 7.98%. Absenteeism PT. Indonesia Power UBP Semarang in 2011 also declined. Employees who off work increased in June. This study aimed to determine the effect of work ability and work motivation on employee performance. The population in this study are 104 operator employees of PT. Indonesia Power UBP Semarang. Sampling technique in this study was saturated sampling. Measurement scale using Likert scale. Data analysis using regression with SPSS 17.0. The results showed that the ability variables have a positive and significant influence on the employees performance at 41.9 percent. Motivation variables have a positive and significant influence on the employees performance at 50.2 percent. Variable work ability and motivation have a positive and significant influence on the performance of employees at 53.5 percent. This study concluded that the ability to work and motivation have a positive and significant influence to the employee performance. PT. Indonesia Power UBP Semarang should provide training to improve the ability, especially in terms of mastery of work equipment and computer systems, understanding of company policies, understanding of corporate objectives and the ability of empathize. Provide better motivation to employees to create a feeling in the employees that they have a role in the company.